Aptamer‐Functionalized Barcodes in Herringbone Microfluidics for Multiple Detection of Exosomes. Issue 6 (24th April 2022) - Chen, Hanxu; Bian, Feika; Guo, Jiahui; Zhao, Yuanjin
Abstract: Tumor‐derived exosomes are vital for clinical dynamic and accurate tumor diagnosis, thus developing sensitive and multiple exosomes detection technology has attracted remarkable attention of scientists. Here, a novel herringbone microfluidic device with aptamer‐functionalized barcodes integration for specific capture and multiple detection of tumor‐derived exosomes is presented. The barcodes with core–shell constructions are obtained by partially replicating the periodically ordered hexagonal close‐packaged colloidal crystal beads. As their inverse opal hydrogel shell possesses rich interconnected pores, the barcodes could provide abundant surface area for functionalization of DNA aptamers to realize specific recognition of target exosomes. Besides, the encoded structure colors of the barcodes can be maintained stably during the detection events as their hardish cores are with sufficient mechanical strength. It is demonstrated that by embedding these barcodes in herringbone groove microfluidic device with designed patterns, the specific capture efficiency and synergetic detection of multiple tumor‐derived exosomes in peripheral blood can be significantly improved due to enhanced resistance of turbulent flow. These features make the aptamer‐functionalized barcodes and herringbone microfluidics integrated platform promising for exosomes extraction and dynamic tumor diagnosis. Abstract : Herringbone microfluidic device integrated with an array of DNA aptamers‐functionalized core–shell structural color hydrogel particle barcodes is presented for capture and multiple detection of tumor‐derived exosomes. The platform exhibits excellent coding stability, high specific capture efficiency, and effective synergetic detection capacity. It is highly promising for exosomes extraction, liquid biopsy, dynamic tumor diagnosis, and individual treatment.